Effect of Casein Tablet Made from Goat Milk Yogurt on Liver Histopathological Profile, Dioxin Residue, and Malondialdehyde level in Broiler Exposed to 2,3,7,8-Tetrachlorodibenzo-P-Dioxin (Faculty of Animal Science Universitas Brawijaya, 2020)
2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is a toxic compound of organic pollutants that is very persistent in the environment. This compound can accumulate in the body through contaminated food and can cause various adverse effects on human health. The purpose of this study was to observe the effect of casein tablets made from goat milk yogurt on Liver histopathological profile, residual TCDD and malondialdehyde (MDA) levels in broiler chicken exposed to 50 ng/mL TCDD. A total of 18 male broiler chickens aged 3 weeks were used in this study and were divided into 3 experimental groups based on a completely randomized design (CRD): 1 (negative control group), 2 (positive control group), 3 (therapeutic group) which were administered by 750 mg of casein from goat milk yogurt for 21 days. TCDD residue and MDA levels in the liver were measured using a UV-Vis spectrophotometer and thiobarbituric acid reactive substances test, respectively. The liver histopathological profile was observed using hematoxylin-eosin staining. The results showed that the administration of casein tablets decreased the level of TCDD residue and MDA by 5.75% and 43.74%, respectively. Moreover, the liver histopathological profile of the therapeutic group was better than that of the positive control group. It is suggested that casein tablet made from goat milk yogurt possesses anti-dioxin and antioxidant capacities.